PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS APLIKASI ANDROID TERHADAP HASIL BELAJAR EKONOMI DENGAN GAYA BELAJAR SEBAGAI VARIABEL MODERATOR (Studi Pada Ma Tawakkal Denpasar Tahun Pelajaran 2020/2021) - Putu Diah Asrida; Ni Luh Putu Cahayani; I Gede Agus Adi Saputra; Teldi Sumarno Boling Sau (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
This study aims to determine the effect of using learning media based on android applications on learning outcomes by using learning styles as a moderating variable. The calculation results obtained a regression coefficient of 2,745, the t-count value is 3,191 and the sig value of 0.002 is smaller than α = 0.05, then Ho is rejected, Ha is accepted. The second hypothesis test states that learning media based on android applications which are moderated by learning styles have a significant effect on learning outcomes with a regression coefficient of -0.030, a t-count value of -2.991 and a significance level of 0.004 which is less than α = 0.05, so it can be it can be concluded that learning styles are able to moderate the effect of android application-based learning media on learning outcomes. With the results of the Adjusted R Square value determination test of 0.709, which means that variations in learning media variables based on android applications and learning styles as well as the interaction between learning media based on android applications and learning styles are able to explain the variable business results by 70.9% and the remaining 29.1% explained by other factors outside this research model.